Patent Ductus Arteriosus Ligation Procedure in a 5 Year Old Girl - Riris Juita Julianty; Didik Haryanto (Institute of Computer Science (IOCS), 2021)
Patent Ductus Arteriosus (PDA) is a congenital heart defect in which the closure of the ductus arteriosus is delayed after 72 hours. The incidence is frequent in the neonatal period and increases with the life expectancy of preterm infants. The clinical symptoms of PDA vary from asymptomatic to clinical heart failure, so PDA is often detected incidentally by echocardiogram. Reported a case of a 5 year old girl who has been known to suffer from PDA from echocardiography examination with a diameter of 3mm PDA. The patient has no complaints other than a continuous sound of heart sounds. Chest X-ray was examined with cardiomegaly results. The patient was treated with surgical ligation. The patient's condition after surgery is stable and there are no complaints.